Représentations des étudiants sur les scientifiques et les savoirs scientifiques : exploration des caractéristiques associées et de leurs spécificités - Laurence Maurines; Magali Fuchs-Gallezot; Marie-Joëlle Ramage (Nantes Université, 2018)
With the prospect of a scientific acculturation for citizenship of all the pupils and of a renewed interest for scientific studies and careers, the official texts at the secondary level education ask more or less explicitly science teachers to help pupils to understand the specificities of sciences as well as the existence of different regimes of truth. We present some of the results to a questionnaire exploring the images of science of 662 freshmen of the scientific university Paris - Sud. We present the multidimensional grid we elaborated to characterize NoS (Nature of Science) by basing our approach on practices. Considering that scientific knowledge is the result of the work driven by persons who act as scientists within a community inscribed in a society and a history, this grid mobilizes all the science studies, in particular the psychology of science. We examine the following questions: how do students characterize the scientific knowledge and what qualities do they attribute to a scientist? How do students consider the specificity of the scientific knowledge with regard to other knowledge ? How do they envisage for an individual the articulation of scientific and religious practices? To what extent their representations of science evoke a rich vision of NoS ? We put in perspective the results obtained with the images of science conveyed by the science programs.